P2.13 Bacterial vaginosis: leading cause of vaginal discharge among women attending sexually transmitted infection clinic in kumasi, ghana. (8th July 2017) - Agyarko-Poku, Thomas; Sarkodie, Yaw Adu; Frempong, Enock Hene
Abstract : Introduction: Vaginal discharge is the most common complaint of women who seek services in the various units in the health delivery system including in most parts of the world. We determine the aetiology of vaginal discharge in women patronising Sexually Transmitted Infection (STI) Clinic in Kumasi, Ghana as a follow up to similar study in 2006. Methods: Specimen for wet mount preparation, pH determination, whiff test, Gram's stain, culture and polymerase chain reaction were collected from the vagina and the cervix of 500 women: 250 sex workers (SW) and 250 non-sex workers (NSW), attending Suntreso STI Clinic in Kumasi, Ghana with complaint of vaginal discharge on their first attendance. Details regarding demographics, symptoms and signs as well as sexual behaviour were recorded. Associations of these factors with each infection were determined and adjusted for other risk factors. Results: 39.4% had bacterial vaginosis (197/500, p-0.000, SW-114/250 {45.2%}; NSW- 83/250{33.2%}, 29.1% with Candida species (145/500: p=0.000, SW- 67/250{26.7%}; NSW- 78/250{31.2%}), 4.5% with Trichomonas vaginalis (23/500: p-0.000 SW-18/250{7.1%; NSW- 5/250{2.0%}, ), 3.1% with Chlamydia trachomatis (16/500: p-0.001 SW-12/250{4.8%}; NSW-4/250{1.6%}), 2.2% with Neisseria gonorrhoeae (11/500: p-0.014, SW- 8/250{3.2%}; NSW- 3/250{0.8%}) and 3.0% with Mycoplasma genitalium (15/500, 3.0%, p-0.000, SW-10/250{4.0%};NSW-5/250{2.0%}). Conclusion: The study found bacterial vaginosis the most predominate aetiological agent of vaginal discharge among women in Kumasi Ghana with an increase in prevalence from 37.8% in 2006 to 39.4% in 2016. The result confirms the existing literature, making the inclusion of bacterial vaginosis in the syndromic management of STI still relevant.